SWOT Analysis and Optimization Strategy Research of China Energy Internet Development in the Intelligent Era - Qin, Xiangchun (International Journal of Computer Science and Information Technology, 2025)
In the context of the ongoing wave of intelligence and urgent energy transformation, China faces the challenge of reducing carbon emissions and optimizing its energy structure. The existing energy system has issues with distribution, transmission, and efficiency, necessitating intelligent innovation. The Energy Internet emerges as a key solution but faces technical challenges, such as inadequate sensing, communication, and energy storage technologies, as well as system, regulatory, and coordination issues within the industry. This study applies SWOT analysis to examine the internal and external factors influencing the Energy Internet and proposes strategies and implementation plans. The research highlights the need for breakthroughs in technology, policy coordination, and business model innovation. By integrating various forces, this approach will help overcome current obstacles and is crucial for advancing energy transformation, improving energy efficiency, ensuring supply stability, and enhancing China’s global energy influence.